2008
DOI: 10.1097/brs.0b013e31818ed8f4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Versus Nonoperative Treatment for Lumbar Disc Herniation

Abstract: fees for product development and royalties for cervical spine implants and femoral ring allograft; Dr. Albert reports receiving reimbursement for attending a symposium, fees for speaking, organizing education, and consulting, and funds for research from DePuy Spine; he has also worked as an independent contractor for DePuy Spine, lecturing on spine topics related to surgery with or without instrumental and molecular biology of the disc. He has received royalties and/ or holds patents for instrumentation that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
137
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(144 citation statements)
references
References 23 publications
4
137
0
2
Order By: Relevance
“…Recently, the overall reoperation rate was reported to be 5.2-19%, whereas the rate of real recurrent herniations, recurrence at the same disc level and same side as the primary herniation, was 3.8-7.4% [2,4,6,7,12]. In 2008, the most reliable rate was reported from the Spine Patient Outcome Research Trial (SPORT), in which additional surgeries occurred in 6% of patients at 1 year postsurgery, 8% at 2 years, 9% at 3 years, and 10% at 4 years, and about half of them were for real recurrent herniations [14]. In those reports, however, some had no data on the population or surgical site or other pathologies such as arachnoiditis or epidural fibrosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, the overall reoperation rate was reported to be 5.2-19%, whereas the rate of real recurrent herniations, recurrence at the same disc level and same side as the primary herniation, was 3.8-7.4% [2,4,6,7,12]. In 2008, the most reliable rate was reported from the Spine Patient Outcome Research Trial (SPORT), in which additional surgeries occurred in 6% of patients at 1 year postsurgery, 8% at 2 years, 9% at 3 years, and 10% at 4 years, and about half of them were for real recurrent herniations [14]. In those reports, however, some had no data on the population or surgical site or other pathologies such as arachnoiditis or epidural fibrosis.…”
Section: Discussionmentioning
confidence: 91%
“…There are many studies on such recurrences in which reoperation rate is reported to be 3.8-24% [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several conditions were involved in these reoperation rates: recurrence at the same disc level and same side as the primary herniation [2,4,9,10,13,14], contralateral herniation at the same disc level [4,6,10,11,13,14], or new herniation at a different spinal level [1,4,9,[12][13][14]. Recurrent herniation at the same level and side as the primary one differs from other conditions because the incision of the posterior longitudinal ligament and annulus during the primary discectomy might be a predisposing factor for recurrence [7].…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of lumbar IVD herniations improve over time or with non-operative therapy, a proportion of patients require surgical intervention [2,3], and some patients may develop a recurrent herniation requiring additional intervention [4]. The U.S. Medicare system spends an estimated $300 million annually on lumbar discectomies [5] and while clinical studies have demonstrated benefits with surgical intervention [2,6,7], the long-term sequelae are unclear and may present with additional clinical problems [8-10]. Costs of managing post-discectomy low back pain were estimated with $4,934 per surgery [10] and therefore are a significant healthcare burden.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal conditions that are most amenable to surgery involve leg-dominant pain (claudication, radiculopathies) of at least 6 weeks' duration with concordant imaging. [6][7][8][9] If patients with back pain who do not require surgery can be reliably distinguished from patients with surgical indications by appropriate medical personnel, the surgically appropriate patient could be fast-tracked for surgical assessment; those without surgical indications could be provided with appropriate education to help understanding, alleviate fears and guide treatment strategies. The presence of red flags for rare and potentially more sinister medical conditions need to be identified, which is mainly done through a focused history.…”
mentioning
confidence: 99%